Longitudinal ex vivo and molecular trends of chloroquine and piperaquine activity against Plasmodium falciparum and P. vivax before and after introduction of artemisinin-based combination therapy in Papua, Indonesia. (December 2021) - Marfurt, Jutta; Wirjanata, Grennady; Prayoga, Pak; Chalfein, Ferryanto; Leonardo, Leo; Sebayang, Boni F.; Apriyanti, Dwi; Sihombing, Maic A.E.M.; Trianty, Leily; Suwanarusk, Rossarin; Brockman, Alan; Piera, Kim A.; et al.
Abstract: Drug resistant Plasmodium parasites are a major threat to malaria control and elimination. After reports of high levels of multidrug resistant P. falciparum and P. vivax in Indonesia, in 2005, the national first-line treatment policy for uncomplicated malaria was changed in March 2006, to dihydroartemisinin-piperaquine against all species. This study assessed the temporal trends in ex vivo drug susceptibility to chloroquine (CQ) and piperaquine (PIP) for both P. falciparum and P. vivax clinical isolates collected between 2004 and 2018, by using schizont maturation assays, and genotyped a subset of isolates for known and putative molecular markers of CQ and PIP resistance by using Sanger and next generation whole genome sequencing. The median CQ IC50 values varied significantly between years in both Plasmodium species, but there was no significant trend over time. In contrast, there was a significant trend for increasing PIP IC50 s in both Plasmodium species from 2010 onwards. Whereas the South American CQ resistant 7G8 pfcrt SVMNT isoform has been fixed since 2005 in the study area, the pfmdr 1 86Y allele frequencies decreased and became fixed at the wild-type allele in 2015. In P. vivax isolates, putative markers of CQ resistance (no pvcrt-o AAG (K10) insertion and pvmdr 1 Y967F and F1076L) were fixed at the mutant alleles since 2005. None of the putative PIP resistance markers were detected in P. falciparum . The ex vivo drug susceptibility and molecular analysis of CQ and PIP efficacy for P. falciparum and P. vivax after 12 years of intense drug pressure with DHP suggests that whilst the degree of CQ resistance appears to have been sustained, there has been a slight decline in PIP susceptibility, although this does not appear to have reached clinically significant levels. The observed decreasing trend in ex vivo PIP susceptibility highlights the importance of ongoing surveillance. Graphical abstract: Image 1